Beyond stability: A study of the impact of politics on foreign direct investment in Mali (2002-2022) - (:unkn) unknown (My University, 2024)
This study examines the impact of politics on Foreign Direct Investment (FDI) in Mali from 2002 to 2022, a period characterized by significant political and economic transformations. The main objective is to determine the extent to which political stability influences FDI flows in a developing African context.Methodologically, this research adopts a mixed approach. It utilizes an Auto-Regressive Distributed Lag (ARDL) model for quantitative analysis of macroeconomic data, and a series of semi-structured interviews with 20 key stakeholders, including business leaders, economists, and policymakers, for in-depth qualitative exploration.The findings reveal that, contrary to expectations, an improvement in political stability does not necessarily correlate with an increase in FDI. In fact, better political stability was correlated with a decrease in long-term FDI, suggesting that investors may favor markets with a certain degree of risk. Additionally, the population (POP) emerged as a constraint on FDI, highlighting the importance of labor quality and internal market development policies.This study enriches the existing literature on FDI in developing countries by providing insights into the complex interplay between politics, economy, and foreign investments in a specific African country. It underscores the importance for policymakers to adopt a holistic approach to attract FDI, going beyond political stability and incorporating economic policies and human capital development.
Keywords: African Research